Pouch film laminate and secondary battery
The pouch film laminate with an optimized yield strength difference between its sealant layers and enhanced peel strength between the gas barrier and sealant layers addresses the issue of poor seal durability in conventional pouch film laminates, resulting in improved sealing strength and battery integrity.
Patent Information
- Application Number
- JP2023570264
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-01
- Filing Date
- 2022-09-28
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-09-28
AI Technical Summary
Conventional pouch film laminates for secondary batteries suffer from poor seal durability due to the separation of the interface between the first and second sealant layers when exposed to harsh environmental conditions or external forces.
The pouch film laminate is designed with a specific structure, including a substrate layer, a gas barrier layer, and a sealant layer with a first and second sealant layer, where the yield strength difference between the two sealant layers is optimized within a range of 66% to 120%, and the peel strength between the gas barrier layer and the first sealant layer is greater than 23N/15mm.
This configuration enhances the sealing strength and durability of the pouch film laminate, ensuring the integrity of the secondary battery even under adverse conditions, with a breaking strength of the seal portion measured at 100N/15mm or more at 25°C and 80N/15mm or more at 60°C.
Smart Images

Figure 0007662837000003 
Figure 0007662837000004 
Figure 0007662837000005
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2021-0131121, filed October 1, 2021, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a pouch film laminate and a secondary battery manufactured by molding the same, and more particularly, to a pouch film laminate that improves the seal strength of a pouch and a secondary battery manufactured by molding the same. [Background technology]
[0003] Generally, types of secondary batteries include nickel-cadmium batteries, nickel-metal hydride batteries, lithium-ion batteries, lithium-ion polymer batteries, etc. These secondary batteries are used not only in small products such as digital cameras, P-DVDs, MP3Ps, mobile phones, PDAs, portable game devices, power tools, and E-bikes, but also in large products that require high output such as electric vehicles and hybrid vehicles, as well as in power storage devices and backup power storage devices that store surplus generated power and new renewable energy.
[0004] To manufacture such a secondary battery, an electrode active material slurry is first applied to a positive electrode current collector and a negative electrode current collector to manufacture a positive electrode and a negative electrode, which are then laminated on both sides of a separator to form an electrode assembly of a predetermined shape, and the electrode assembly is then housed in a battery case, an electrolyte is injected, and the battery case is sealed.
[0005] Secondary batteries are classified into pouch type and can type depending on the material of the case that houses the electrode assembly. The pouch type houses the electrode assembly in a pouch made of flexible polymer material, while the can type houses the electrode assembly in a case made of metal, plastic, or other material.
[0006] A pouch, which is a case for a pouch-type secondary battery, is manufactured by pressing a flexible pouch film laminate to form a cup portion. When the cup portion is formed, an electrode assembly is placed in the inner accommodating space of the cup portion and the seal portion is sealed to manufacture a secondary battery.
[0007] In general, a pouch film laminate is formed of multiple layers, with a polymer film such as polyethylene terephthalate laminated on one side of a metal gas barrier layer and a sealant layer laminated on the other side. However, in the case of such a conventional pouch film laminate, when a pouch-type secondary battery is exposed to harsh environmental conditions, the sealed portion of the pouch may be vented, which may cause contamination or functional failure of the electrode assembly housed inside the pouch. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides a pouch film laminate with improved pouch seal strength by optimizing the yield strength of the sealant layer.
[0009] The object of the present invention is not limited to the above-mentioned objects, and other objects not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]
[0010] A pouch film laminate according to one embodiment of the present invention has a base layer, a gas barrier layer, and a sealant layer laminated in that order, the sealant layer including a first sealant layer disposed adjacent to the gas barrier layer, and a second sealant layer laminated on the first sealant layer, and ΔY according to the following formula 1 is 66% to 120%.
[0011] [Number 1] ΔY={(yield strength of second sealant layer - yield strength of first sealant layer) / yield strength of first sealant layer}×100
[0012] In the pouch film laminate of the present invention, the difference in yield strength between the first sealant layer and the second sealant layer may be 8 N / 15 mm or less.
[0013] In the pouch film laminate of the present invention, the yield strength of the first sealant layer may be lower than the yield strength of the second sealant layer.
[0014] In the pouch film laminate of the present invention, the first sealant layer may have a yield strength of 7 N / 15 mm to 15 N / 15 mm.
[0015] In the pouch film laminate of the present invention, the second sealant layer may have a yield strength of 10 N / 15 mm to 30 N / 15 mm.
[0016] In the pouch film laminate of the present invention, the thickness ratio of the first sealant layer to the second sealant layer may be 1:0.3 to 1:3.
[0017] In the pouch film laminate of the present invention, the first sealant layer may have a thickness of 10 μm to 60 μm.
[0018] In the pouch film laminate of the present invention, the second sealant layer may have a thickness of 20 μm to 70 μm.
[0019] In the pouch film laminate of the present invention, the first sealant layer and the second sealant layer may contain polypropylene (PP), and the gas barrier layer may contain aluminum (Al).
[0020] In the pouch film laminate of the present invention, the peel strength between the gas barrier layer and the first sealant layer may exceed 23 N / 15 mm.
[0021] When two of the pouch film laminates are laminated so that the second sealant layers of each are in contact with each other, and then sealed for two seconds under conditions of 180°C and 0.4 MPa to form a sealed portion, the breaking strength of the sealed portion measured at 25°C may be 100N / 15mm or more, and the breaking strength of the sealed portion measured at 60°C may be 80N / 15mm or more.
[0022] Meanwhile, a secondary battery according to another embodiment of the present invention includes a pouch-type battery case manufactured by molding any one of the above-mentioned pouch film laminates, and an electrode assembly housed inside the pouch-type battery case. Effect of the Invention
[0023] Conventionally, when manufacturing a pouch film laminate, the first sealant layer attached to the gas barrier layer is generally formed from a material having lower fluidity than the second sealant layer in order to improve the adhesive strength with the gas barrier layer, which is a metal layer. However, in the case of a battery case manufactured using such a conventional pouch film laminate, when gas is generated inside the pouch or an external force is applied, there is a problem that the interface between the first sealant layer and the second sealant layer peels off, resulting in poor seal durability.
[0024] In order to solve the above problems, the pouch film laminate according to the present invention controls the difference in yield strength between the first sealant layer and the second sealant layer within a specific range, thereby making it possible to suppress peeling at the interface between the first sealant layer and the second sealant layer due to external forces, gas generation, etc. This improves the seal durability of a pouch produced by sealing the pouch film laminate. [Brief description of the drawings]
[0025] [Figure 1] 1 is a cross-sectional view of a pouch film laminate according to the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a seal portion of a pouch-type battery case according to the present invention. [Diagram 3] FIG. 2 is an exploded view of a secondary battery according to the present invention. [Figure 4] FIG. 2 is a diagram showing how to measure the peel strength between a gas barrier layer and a sealant layer according to the present invention. [Diagram 5] FIG. 2 is a diagram showing how to measure the breaking strength of a seal portion produced from a pouch film laminate according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The advantages and features of the present invention, as well as the methods for achieving them, will become apparent from the following detailed description of the embodiments in conjunction with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below, and can be realized in various different forms. The present embodiments are provided merely to complete the disclosure of the present invention and to allow those skilled in the art to fully understand the scope of the invention, and the present invention is only defined by the claims. The same reference numerals refer to the same elements throughout the specification.
[0027] Unless otherwise defined, all terms (including technical and scientific terms) used in this specification will be used in the sense commonly understood by those having ordinary skill in the art to which the present invention belongs. Furthermore, terms defined in commonly used dictionaries will not be interpreted ideally or excessively unless clearly and specifically defined.
[0028] The terms used in this specification are for the purpose of describing the embodiments, and are not intended to limit the present invention. In this specification, the singular form includes the plural form unless otherwise specified. As used in this specification, "comprises" and / or "comprising" do not exclude the presence or addition of one or more other components in addition to the components mentioned.
[0029] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings.
[0030] In this specification, when a part includes a certain component, it means that it may further include other components, not excluding other components, unless specifically stated to the contrary.
[0031] In this specification, the upper part of a drawing may be referred to as the "upper part" or "upper side" of the configuration shown in the drawing, and the lower part may be referred to as the "lower part" or "lower side". In addition, the part between the upper and lower parts of the configuration shown in the drawing, or the other part excluding the upper and lower parts, may be referred to as the "side" or "side surface". Such relative terms such as "upper part" and "upper side" are used to describe the relationship between the configurations shown in the drawings, and the present disclosure is not limited by such terms.
[0032] In this specification, a direction toward an internal space of a structure is referred to as an "inside" and a direction protruding into an open external space is referred to as an "outside." Relative terms such as "inside" and "outside" are used to describe the relationship between components shown in the drawings, and the present disclosure is not limited by such terms.
[0033] In this specification, the phrase "A and / or B" means A, or B, or A and B.
[0034] In this specification, when a part is said to be connected to another part, this does not only mean that they are directly connected to each other, but also means that they are connected via another structure between them.
[0035] In this specification, yield strength is the limit stress at which elastic deformation occurs, and means a 0.2% offset stress. It is measured by pulling a 15 mm x 80 mm polypropylene film sample at a speed of 50 mm / min in an environment of 25°C and 40% relative humidity using a UTM measuring device (Zwick).
[0036] In this specification, the breaking strength of the seal portion means the stress at which the seal portion formed by laminating two pouch film laminates so that their second sealant layers are in contact with each other and then sealing for 2 seconds under the conditions of 180°C and 0.4 MPa breaks. Specifically, the breaking strength of the seal portion means the maximum tensile strength measured when the seal portion breaks after cutting the sample with the seal portion formed thereon to a width of 15 mm, fastening one end of each of the pouch film laminates laminated above and below in the sample to the upper and lower jigs of a measuring device (UTM, Zwick) and pulling it vertically at a speed of 5 mm / min.
[0037] Pouch film laminate The pouch film laminate according to the present invention is a laminate comprising a base layer, a gas barrier layer, and a sealant layer laminated in this order, wherein the sealant layer includes a first sealant layer disposed adjacent to the gas barrier layer, and a second sealant layer laminated on the first sealant layer, and ΔY according to the following formula 1 is 66% to 120%.
[0038] [Number 1] ΔY={(yield strength of second sealant layer - yield strength of first sealant layer) / yield strength of first sealant layer}×100
[0039] Hereinafter, the pouch film laminate according to the present invention and each layer contained in the pouch film laminate will be described in detail with reference to FIG.
[0040] FIG. 1 is a cross-sectional view of a pouch film laminate 100 according to the present invention.
[0041] 1, the pouch film laminate 100 includes a base layer 110, a gas barrier layer 120, and a sealant layer 130, and the sealant layer 130 includes a first sealant layer 132 and a second sealant layer 134. In the pouch film laminate 100, the base layer 110, the gas barrier layer 120, the first sealant layer 132, and the second sealant layer 134 may be laminated in sequence.
[0042] (1) Base material layer The base layer 110 is formed on the outermost layer of the pouch film laminate 100 to protect the secondary battery from external friction and impact. The base layer 110 is made of a polymer and can electrically insulate the electrode assembly from the outside. The base layer 110 may be made of one or more materials selected from the group consisting of, for example, polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, acrylic polymer, polyacrylonitrile, polyimide, polyamide, cellulose, aramid, nylon, polyester, polyparaphenylene benzobisoxazole, polyarylate, Teflon (registered trademark), and glass fiber. Among them, it is particularly preferable that the base layer 110 is made of polyethylene terephthalate (PET), nylon, or a combination thereof, which has abrasion resistance and heat resistance.
[0043] The substrate layer 110 may have a single film structure made of any one material, or alternatively, the substrate layer 110 may have a composite film structure formed by layers of two or more materials.
[0044] The thickness of the base layer 110 may be 5 μm to 50 μm, specifically 7 μm to 50 μm, and more specifically 7 μm to 40 μm. When the thickness of the base layer 110 satisfies the above range, the pouch film laminate has excellent external insulation properties, and the thickness of the entire pouch does not increase, so that the secondary battery has excellent energy density relative to its volume.
[0045] (2) Gas barrier layer The gas barrier layer 120 is laminated between the base layer 110 and the sealant layer 130 to ensure the mechanical strength of the pouch, block the entry and exit of gas, moisture, and the like from the outside of the pouch-type battery case, and prevent electrolyte leakage from the inside of the pouch-type battery case.
[0046] The gas barrier layer 120 may be made of a metal, specifically, an aluminum alloy thin film. When the gas barrier layer is formed using an aluminum alloy thin film, it is possible to ensure a certain level of mechanical strength, a light weight, and a complement of the electrochemical properties of the electrode assembly and the electrolyte, as well as heat dissipation. The aluminum alloy thin film may contain one or more metal elements other than aluminum, such as iron (Fe), copper (Cu), chromium (Cr), manganese (Mn), nickel (Ni), magnesium (Mg), silicon (Si), and zinc (Zn).
[0047] On the other hand, the thickness of the gas barrier layer 120 may be 40 μm to 100 μm, specifically 50 μm to 90 μm, and more specifically 55 μm to 85 μm. When the thickness of the gas barrier layer 120 satisfies the above range, the moldability during molding of the cup portion and the gas barrier performance are excellent.
[0048] (3) Sealant layer The sealant layer 130 is for completely sealing the inside of the pouch-type battery case from the outside by thermally bonding the seal parts (350 in FIG. 3) together when the pouch-type battery case (310 in FIG. 3) that houses the electrode assembly inside is sealed. For this reason, the sealant layer 130 may be made of a material having excellent thermal bonding strength.
[0049] The sealant layer 130 may have a composite film structure formed from layers of two or more materials.
[0050] Specifically, the sealant layer 130 according to the present invention may include a first sealant layer 132 and a second sealant layer 134. In this case, the first sealant layer 132 may be a layer disposed adjacent to the gas barrier layer 120, and the second sealant layer 134 may be a layer disposed on the first sealant layer 132. The first sealant layer 132 and the second sealant layer 134 may be made of materials having different materials and / or physical properties.
[0051] There may be an interface between the first sealant layer 132 and the second sealant layer 134. This means that the first sealant layer 132 and the second sealant layer 134 are different layers and may be formed separately.
[0052] According to the present invention, ΔY according to the following formula 1 may be 66% to 120%, specifically 66% to 110%, and more specifically 66% to 100%, where ΔY refers to a value expressed as a percentage of the difference between the yield strength of the first sealant layer 132 and the yield strength of the second sealant layer 134 relative to the yield strength of the first sealant layer 132.
[0053] [Number 1] ΔY={(yield strength of second sealant layer - yield strength of first sealant layer) / yield strength of first sealant layer}×100
[0054] If ΔY exceeds 120%, the possibility of delamination occurring at the interface between the first sealant layer 132 and the second sealant layer 134 increases when an external force or gas is generated, and the seal durability of the pouch-type battery case (310 in FIG. 3) may decrease.
[0055] If ΔY is less than 66%, the extrusion processability of the sealant layer during the production of the pouch film laminate may be reduced, and the low-temperature sealability may be reduced during the sealing process for battery production after the production of the pouch film laminate.
[0056] The difference in yield strength between the first sealant layer 132 and the second sealant layer 134 may be 8 N / 15 mm or less, preferably 1 N / 15 mm to 8 N / 15 mm, and more preferably 3 N / 15 mm to 7 N / 15 mm. When the difference in yield strength between the first sealant layer 132 and the second sealant layer 134 satisfies the above range, there is a low possibility that delamination will occur at the interface between the first sealant layer 132 and the second sealant layer 134 when an external force is applied or gas is generated, and the seal durability of the pouch-type battery case (310 in FIG. 3) is improved.
[0057] The yield strength of the first sealant layer 132 may be lower than the yield strength of the second sealant layer 134. In this case, the first sealant layer 132 has lower fluidity than the second sealant layer 134, and is therefore easily attached to the gas barrier layer 120 when the pouch film laminate 100 is formed, and the adhesive strength at the interface between the gas barrier layer 120 and the first sealant layer 132 is maintained high when an external force is applied.
[0058] The first sealant layer 132 and the second sealant layer 134 may be made of materials having different materials and / or physical properties. For example, the first sealant layer 132 may be made of a material having lower fluidity than the second sealant layer 134. In this case, the first sealant layer 132 having lower fluidity has a lower yield strength than the second sealant layer 134.
[0059] The thickness ratio of the first sealant layer 132 to the second sealant layer 134 may be 1:0.3 to 1:3, preferably 1:0.6 to 1:2.2, and more preferably 1:1 to 1:1.7. When the thickness ratio of the first sealant layer 132 to the second sealant layer 134 satisfies the above range, the extrusion processability between the gas barrier layer 120 and the sealant layer 130 can be ensured, and at the same time, the effect of improving the breaking strength of the seal portion can be obtained.
[0060] Each of the first sealant layer 132 and the second sealant layer 134 will now be described in more detail.
[0061] 1) First sealant layer The first sealant layer 132 may be a layer disposed adjacent to the gas barrier layer 120, as previously described.
[0062] The first sealant layer 132 may be made of a polymer material. Specifically, the first sealant layer 132 may be made of one or more materials selected from the group consisting of polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, acrylic polymers, polyacrylonitrile, polyimide, polyamide, cellulose, aramid, nylon, polyester, polyparaphenylene benzobisoxazole, polyarylate, Teflon (registered trademark), and glass fiber, and is preferably made of a polyolefin resin such as polypropylene (PP) and / or polyethylene (PE). In this case, the polypropylene may be made of cast polypropylene (CPP), acid modified polypropylene (Acid Modified Polypropylene, PPa), or polypropylene-butylene-ethylene terpolymer.
[0063] It is particularly preferable that the first sealant layer 132 is made of acid-modified polypropylene (PPa) in order to ensure long-term adhesion performance between the gas barrier layer 120 and the first sealant layer 132. Here, the acid-modified polypropylene may be maleic anhydride polypropylene (MAH PP).
[0064] In order to adjust the yield strength of the first sealant layer 132 to a desired value, an additive may be added to the polymer material forming the first sealant layer 132. For example, at least one of carbon fiber, glass fiber, and aramid fiber may be added as an additive to improve the yield strength of the first sealant layer 132. For example, the additive may be included in an amount of 5 vol % to 8 vol % based on the total volume of the first sealant layer, but is not limited thereto.
[0065] The yield strength of the first sealant layer 132 may be 7N / 15mm to 15N / 15mm, preferably 7.2N / 15mm to 9.0N / 15mm, and more preferably 7.5N / 15mm to 8.5N / 15mm.
[0066] If the yield strength of the first sealant layer 132 is less than 7 N / 15 mm, the difference in yield strength between the first sealant layer 132 and the second sealant layer 134 will be large, which may cause delamination at the interface between the first sealant layer 132 and the second sealant layer 134 when an external force is applied or gas is generated, thereby reducing the seal durability of the pouch-type battery case (310 in Figure 3).
[0067] If the yield strength of the first sealant layer 132 exceeds 15 N / 15 mm, the extrusion process for laminating the gas barrier layer 120 and the first sealant layer 132 may be deteriorated. In addition, in order to increase the yield strength of the first sealant layer 132, it is necessary to improve the overall strength of the sealant layer 130, but when the first sealant layer 132 and the second sealant layer 134 are extruded for this purpose, problems such as the occurrence of a necking phenomenon may occur. In addition, as the difference between the yield strength of the first sealant layer 132 and the yield strength of the gas barrier layer 120 becomes large, the adhesive strength at the interface between the gas barrier layer 120 and the first sealant layer 132 may be reduced.
[0068] The thickness of the first sealant layer 132 may be 10 μm to 60 μm, preferably 20 μm to 50 μm, and more preferably 30 μm to 40 μm. If the thickness of the first sealant layer 132 is thinner than 10 μm, there is a problem that the seal durability and insulation of the seal part (350 in FIG. 3) are reduced, and the yield strength of the first sealant layer 132 is reduced, resulting in a weakened seal strength of the seal part (350 in FIG. 3). If the thickness of the first sealant layer 132 is thicker than 60 μm, the overall thickness of the pouch film laminate becomes too thick, resulting in a reduced formability, and in a pouch-type battery case manufactured by molding the pouch film laminate, the storage space (324 in FIG. 3) for the electrode assembly is reduced, which may result in a reduced energy density relative to the volume of the secondary battery.
[0069] 2) No. 2 Sealant Layer The second sealant layer 134 may be a layer disposed over the first sealant layer 132, as previously described.
[0070] The second sealant layer 134 may be made of a material having insulating properties, corrosion resistance, and sealing properties. Specifically, referring to Fig. 3, the second sealant layer 134 is in direct contact with the electrode assembly (360 in Fig. 3) and / or the electrolyte inside the receiving space (324 in Fig. 3), and therefore may be made of a material having insulating properties and corrosion resistance. In addition, the second sealant layer 134 must completely seal the inside of the pouch-type battery case to prevent the movement of materials between the inside and outside, and therefore may be made of a material having high sealing properties (e.g., excellent thermal adhesive strength).
[0071] In order to ensure such insulation, corrosion resistance, and sealing properties, the second sealant layer 134 may be made of a polymer material. Specifically, the second sealant layer 134 may be made of one or more materials selected from the group consisting of polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, acrylic polymer, polyacrylonitrile, polyimide, polyamide, cellulose, aramid, nylon, polyester, polyparaphenylene benzobisoxazole, polyarylate, Teflon (registered trademark), and glass fiber. The second sealant layer 134 is preferably made of a polyolefin resin such as polypropylene (PP) and / or polyethylene (PE). In this case, the polypropylene may be made of unstretched polypropylene, acid modified polypropylene, or polypropylene-butylene-ethylene terpolymer. Here, the acid modified polypropylene may be maleic anhydride polypropylene (MAH PP). The second sealant layer 134 is more preferably made of unstretched polypropylene having heat sealing properties and high tensile strength.
[0072] In order to adjust the yield strength of the second sealant layer 134 to a desired value, an additive may be added to the polymer material forming the second sealant layer 134. For example, at least one of carbon fiber, glass fiber, and aramid fiber may be added as an additive to improve the yield strength of the second sealant layer 134.
[0073] The yield strength of the second sealant layer 134 may be 10N / 15mm to 30N / 15mm, specifically 12N / 15mm to 17N / 15mm, and more specifically 14N / 15mm to 16N / 15mm. If the yield strength of the second sealant layer 134 is less than 10N / 15mm, a fracture may occur along the sealed pair of second sealant layers 134 when an external force or gas is generated, and the seal durability of the pouch-type battery case (310 in FIG. 3) may decrease. If the yield strength of the second sealant layer 134 exceeds 30N / 15mm, the difference between the yield strength of the second sealant layer 134 and the yield strength of the first sealant layer 132 becomes large, and the risk of peeling occurring at the interface between the first sealant layer 132 and the second sealant layer 134 increases.
[0074] The thickness of the second sealant layer 134 may be 20 μm to 70 μm, preferably 30 μm to 70 μm, and more preferably 40 μm to 60 μm. If the thickness of the second sealant layer 134 is thinner than 20 μm, the seal durability and insulation of the seal part (350 in FIG. 3) may decrease, and the yield strength of the second sealant layer 134 may decrease, resulting in a problem of weakening the seal strength of the seal part (350 in FIG. 3). If the thickness of the second sealant layer 134 is thicker than 70 μm, the overall thickness of the pouch film laminate may become too thick, resulting in a decrease in formability, and in a pouch-type battery case manufactured by molding the pouch film laminate, the storage space (324 in FIG. 3) for the electrode assembly may decrease, resulting in a decrease in the energy density relative to the volume of the secondary battery.
[0075] Next, FIG. 2 is a cross-sectional view showing a seal portion 210 of a pouch-type battery case according to the present invention.
[0076] 2, the battery case manufactured by molding the pouch film laminate may be sealed after being laminated so that the second sealant layer 134 abuts against the first sealant layer 134. In this case, the seal portion 210 includes one or more sealant layers 130.
[0077] When pressure is applied to the sealed battery case due to an external force, gas generation, etc., peeling occurs at interfaces between layers with relatively weak adhesion, such as along the interface between the gas barrier layer 120 and the first sealant layer 132 (e.g., path A in FIG. 2), the interface between the second sealant layers 134 that are thermally bonded to each other (e.g., path B in FIG. 2), and / or the interface between the first sealant layer 132 and the second sealant layer 134 (e.g., path C in FIG. 2).
[0078] However, the battery case manufactured using the pouch film laminate according to the present invention has excellent adhesive strength at all three interfaces, and exhibits excellent seal strength.
[0079] Specifically, in the pouch film laminate of the present invention, the yield strength of the first sealant layer 132 is approximately equal to the yield strength of the gas barrier layer 120, so that when an external force is applied, the adhesive strength at the interface between the gas barrier layer 120 and the first sealant layer 132 is maintained high, and peeling is suppressed. For example, the peel strength between the gas barrier layer 120 and the first sealant layer 132 may exceed 23 N / 15 mm, preferably 23.2 N / 15 mm or more, and more preferably 23.5 N / 15 mm or more. When the peel strength between the gas barrier layer 120 and the first sealant layer 132 satisfies the above range, peeling is suppressed at the interface between the gas barrier layer 120 and the first sealant layer 132.
[0080] In addition, since the second sealant layer 134 formed in the seal portion 210 has a high yield strength, a high restoring force acts when an external force is applied, so that interfacial peeling between the second sealant layers 134 that are thermally bonded to each other is suppressed.
[0081] In addition, because the difference in yield strength between the first sealant layer 132 and the second sealant layer 134 is small, delamination at the interface between the first sealant layer 132 and the second sealant layer 134 is suppressed.
[0082] According to one embodiment of the present invention, the sealing portion 210 may be formed by laminating two pouch film laminates so that their second sealant layers 134 abut, and then sealing them for two seconds under conditions of 180°C and 0.4 MPa.
[0083] In this case, the breaking strength of the seal portion 210 measured at 25° C. may be 100 N / 15 mm or more, preferably 110 N / 15 mm or more, and more preferably 120 N / 15 mm or more.
[0084] Furthermore, the breaking strength of the seal portion 210 measured at 60° C. may be 80 N / 15 mm or more, preferably 90 N / 15 mm or more, and more preferably 100 N / 15 mm or more.
[0085] If the breaking strength of the seal portion 210 at 25°C is less than 100 N / 15 mm, or if the breaking strength of the seal portion 210 at 60°C is less than 80 N / 15 mm, the sealing strength of the seal portion 210 is low, and there is a problem that the sealed battery case is easily vented due to external forces, gas generation, etc.
[0086] The breaking strength of the sealed portion 210 means the maximum tensile strength measured when one end of each of the pouch film laminates stacked vertically in the sample having the sealed portion 210 is fastened to the upper / lower fixture of a measuring device and pulled vertically at a speed of 5 mm / min until the sealed portion is broken. In addition, the "25°C" and "60°C" mean the temperatures when one end of each of the adjacently arranged pouch film laminates 100 is pulled vertically.
[0087] secondary battery Next, the secondary battery according to the present invention will be described.
[0088] FIG. 3 is an exploded view of a secondary battery 300 according to the present invention.
[0089] 3, a secondary battery 300 according to the present invention may include a pouch-type battery case 310 and an electrode assembly 360 housed in the pouch-type battery case 310. The electrode assembly 360 may be formed by stacking a positive electrode, a separator, and a negative electrode, and may include an electrode tab 370, an electrode lead 380, and an insulating part 390. The secondary battery 300 may be manufactured by injecting an electrolyte with the electrode assembly 360 housed inside the pouch-type battery case 310 and then sealing the seal part 350.
[0090] The pouch-type battery case 310 may house the electrode assembly 360 inside. The pouch-type battery case 310 may be manufactured by molding the pouch film laminate 100 of Fig. 1 described above. The detailed configuration and physical properties of the pouch film laminate 100 are as described above, so a detailed description will be omitted.
[0091] To manufacture the pouch-type battery case 310, the pouch-type film laminate 100 may be drawn and stretched using a punch or the like to form a cup portion 322 including a pocket-shaped storage space 324 capable of accommodating the electrode assembly 360.
[0092] As shown in Fig. 3, the pouch-type battery case 310 may include a first case 320 and a second case 330. In one embodiment, the first case 320 includes a receiving space 324 in which a cup portion 322 is formed and capable of receiving an electrode assembly 360, and the second case 330 may cover the receiving space 324 from above so that the electrode assembly 360 does not fall out of the battery case 310. The first case 320 and the second case 330 may be manufactured by connecting one side to each other (e.g., reference numeral 340) as shown in Fig. 3, but the present invention is not limited thereto, and the first case 320 and the second case 330 may be manufactured in various forms, such as being separated from each other and separately manufactured.
[0093] In another embodiment, when the cup portion 322 is formed in the pouch film laminate 100, two symmetrical cup portions 322, 332 may be adjacently formed in one pouch film laminate 100 by drawing. In this case, the first case 320 and the second case 330 may be formed with the cup portions 322, 332, respectively, as shown in FIG. 3. The electrode assembly 360 may be stored in the storage space 324 provided in the cup portion 322 of the first case 320, and then the bridge portion 340 formed between the two cup portions 322, 332 may be folded so that the two cup portions 322, 332 face each other. In this case, the cup portion 332 of the second case 330 can store the electrode assembly 360 from above. Therefore, since the two cup portions 322, 332 store one electrode assembly 360, it is possible to store a thicker electrode assembly 360 than when there is only one cup portion 322. In addition, since one edge of the secondary battery 300 is formed by folding the pouch-type battery case 310, the number of edges to be sealed in a later sealing process is reduced, thereby improving the processing speed of the secondary battery 300 and reducing the number of sealing processes.
[0094] The pouch-type battery case 310 may be sealed in a state in which the electrode assembly 360 is housed so that a part of the electrode lead 380, i.e., a terminal part, is exposed. Specifically, when the electrode lead 380 is connected to the electrode tab 370 of the electrode assembly 360 and an insulating part 390 is formed on a part of the electrode lead 380, the electrode assembly 360 may be housed in the housing space 324 provided in the cup part 322 of the first case 320, and the housing space 324 may be covered from above by the second case 330. Then, an electrolyte may be injected into the housing space 324, and the seal part 350 formed on the edge part of the first case 320 and the second case 330 may be sealed. The electrolyte is for moving lithium ions generated by an electrochemical reaction of the electrodes during charging / discharging of the secondary battery 300, and may include a non-aqueous organic electrolyte solution that is a mixture of a lithium salt and an organic solvent, or a polymer using a polymer electrolyte. Furthermore, the electrolyte may include a sulfide-based, oxide-based, or polymer-based solid electrolyte, and such a solid electrolyte has flexibility and is easily deformed by an external force.
[0095] Next, the electrode assembly 360 may be formed by alternately stacking the electrodes and the separators. Specifically, the electrode assembly 360 may be formed in a predetermined shape by coating a slurry of an electrode active material, a binder, and / or a conductive material on a positive electrode collector and a negative electrode collector to prepare a positive electrode and a negative electrode, and stacking them on both sides of a separator. The electrode assembly 360 may be inserted into a pouch-type battery case 310, and may be sealed by the pouch-type battery case 310 after an electrolyte is injected. In an embodiment, the type of the electrode assembly 360 may be, but is not limited to, a stack type, a jelly roll type, a stack-and-fold type, and the like.
[0096] In one embodiment, the electrode assembly 360 may include two types of electrodes, a positive electrode and a negative electrode, and a separator interposed between the electrodes to insulate the electrodes from each other. The positive electrode and the negative electrode each have a structure in which an active material slurry is applied to an electrode collector in the form of a metal foil or metal mesh containing aluminum and copper. The slurry may be formed by stirring a granular active material, an auxiliary conductor, a binder, a conductive material, etc., in a state where a solvent is added. The solvent is removed in a subsequent process.
[0097] The electrode tabs 370 are connected to the positive and negative electrodes of the electrode assembly 360, protrude from the electrode assembly 360, and serve as a path for electrons to move between the inside and outside of the electrode assembly 360. The electrode current collector of the electrode assembly 360 may be composed of a portion coated with an electrode active material and an end portion, i.e., a plain portion, where the electrode active material is not coated. The electrode tabs 370 may be formed by cutting the plain portion, or by connecting a separate conductive member to the plain portion by ultrasonic welding or the like. As shown in FIG. 3, the electrode tabs 370 may protrude in different directions from the electrode assembly 360, but are not limited thereto, and may be formed to protrude in various directions, such as protruding in the same direction from one side.
[0098] The electrode lead 380 may supply electricity to the outside of the secondary battery 300. The electrode lead 380 may be connected to the electrode tab 370 of the electrode assembly 360 by spot welding or the like. At least a portion of the electrode lead 380 may be surrounded by an insulating portion 390. In an embodiment, the electrode lead 380 may have one end connected to the electrode tab 370 and the other end protruding to the outside of the battery case 310. The electrode lead 380 may include a positive electrode lead 382 having one end connected to the positive electrode tab 372 and extending in the direction in which the positive electrode tab 372 protrudes, and a negative electrode lead 384 having one end connected to the negative electrode tab 374 and extending in the direction in which the negative electrode tab 374 protrudes.
[0099] The other end of each of the positive electrode lead 382 and the negative electrode lead 384 may protrude to the outside of the battery case 310. In this way, electricity generated inside the electrode assembly 360 can be supplied to the outside. In addition, since the positive electrode tab 372 and the negative electrode tab 374 are respectively protruded in various directions, the positive electrode lead 382 and the negative electrode lead 384 can also extend in various directions. In one embodiment, the positive electrode lead 382 and the negative electrode lead 384 may be made of different materials. That is, the positive electrode lead 382 may be made of the same aluminum (Al) material as the positive electrode current collector, and the negative electrode lead 384 may be made of the same copper (Cu) material as the negative electrode current collector or a copper material coated with nickel (Ni). A portion of the electrode lead 380 protruding to the outside of the battery case 310 may become a terminal portion and be electrically connected to an external terminal.
[0100] The insulating part 390 can adhere the electrode lead 380 to the battery case 310 in a state where it is limited to the seal part 350 where the first case 320 and the second case 330 of the pouch-type battery case 310 are heat-sealed. In addition, the insulating part 390 can prevent electricity generated from the electrode assembly 360 from flowing to the battery case 310 through the electrode lead 380, and can maintain the seal of the battery case 310. For this purpose, the insulating part 390 may be manufactured from a non-conductor having non-conductivity that does not easily pass electricity. Generally, as the insulating part 390, an insulating tape that is easy to attach to the electrode lead 380 and has a relatively thin thickness is often used, but the insulating part 390 is not limited thereto, and any member that insulates the electrode lead 380 may be used.
[0101] The present invention will be described in more detail below with reference to specific examples. However, the following examples are merely illustrative to aid in understanding the present invention and are not intended to limit the scope of the present invention. It is obvious to those skilled in the art that various changes and modifications are possible within the scope of the present description and technical ideas, and it is self-evident that such changes and modifications are included in the scope of the appended claims. EXAMPLES
[0102] Examples and Comparative Examples Example 1 (Production of Pouch Film Laminate) A polyethylene terephthalate film measuring 266 mm wide, 50 m long and 12 μm thick and a nylon film measuring 266 mm wide, 50 m long and 25 μm thick were laminated on one side of an aluminum alloy thin film measuring 266 mm wide, 50 m long and 60 μm thick, and an acid-modified polypropylene (PPa) film measuring 266 mm wide, 50 m long and 30 μm thick and a non-oriented polypropylene (CPP) film measuring 266 mm wide, 50 m long and 50 μm thick were laminated on the other side to produce a pouch film laminate with a polyethylene terephthalate / nylon / aluminum alloy thin film / acid-modified polypropylene / non-oriented polypropylene structure.
[0103] In this case, 8 vol% of carbon fiber additive to improve yield strength was added to the acid-modified polypropylene, and the acid-modified polypropylene was melted at high temperature and then extruded onto the aluminum alloy thin film and unstretched polypropylene for lamination.
[0104] Here, the polyethylene terephthalate and nylon are the base layer, the aluminum alloy thin film is the gas barrier layer, the acid-modified polypropylene is the first sealant layer, and the unstretched polypropylene is the second sealant layer.
[0105] Example 2 (Production of Pouch Film Laminate) A pouch film laminate was produced in the same manner as in Example 1, except that 5 vol% of a carbon fiber additive for improving yield strength was added to the first sealant layer.
[0106] Comparative Example 1 (Production of Pouch Film Laminate) A pouch film laminate was produced in the same manner as in Example 1, except that no additive for improving the yield strength was added to the first sealant layer.
[0107] Comparative Example 2 (Production of Pouch Film Laminate) A pouch film laminate was produced in the same manner as in Comparative Example 1, except that the first sealant layer was formed to a thickness of 20 μm.
[0108] Comparative Example 3 (Production of Pouch Film Laminate) A pouch film laminate was produced in the same manner as in Comparative Example 1, except that 10 vol % of a carbon fiber additive for improving yield strength was added to the first sealant layer.
[0109] The materials and thicknesses of each layer of the pouch film laminates produced in Examples 1 and 2 and Comparative Examples 1 to 3 are as shown in Table 1 below.
[0110] [Table 1]
[0111] Experimental Example 1: Measurement of the yield strength of the sealant layer In the examples and comparative examples, the resins constituting the first and second sealant layers were extruded into a film, and then the stress-strain curves were measured to measure the yield strengths of the first and second sealant layers. The measured yield strengths were then used to calculate ΔY according to the following formula 1. The yield strengths and ΔY values are shown in Table 2 below.
[0112] [Number 1] ΔY={(yield strength of second sealant layer - yield strength of first sealant layer) / yield strength of first sealant layer}×100
[0113] Experimental Example 2: Evaluation of peel strength between gas barrier layer and sealant layer For each of the pouch film laminates produced in the Examples and Comparative Examples, the peel strength between the gas barrier layer and the sealant layer was measured.
[0114] Specifically, the 180 degree peel strength was measured by peeling the sealant layer from each of the pouch film laminates manufactured in the examples and comparative examples as shown in Figure 4, and the average strength of the flat section from 5 to 25 mm was measured. The measurement results are shown in Table 2 below.
[0115] FIG. 4 shows how the peel strength between the gas barrier layer and the sealant layer according to the present invention is measured.
[0116] Experimental Example 3: Evaluation of the Presence or Absence of Delamination between the First and Second Sealant Layers The presence or absence of delamination between the first sealant layer and the second sealant layer was confirmed with the naked eye when measuring the peel strength between the gas barrier layer and the sealant layer in Experimental Example 2. The measurement results are shown in Table 2 below.
[0117] Experimental example 4: Evaluation of the breaking strength of the seal Two pouch film laminates manufactured in each of the examples and comparative examples were laminated so that the second sealant layers were in contact with each other. Then, the sealant layers were sealed for 2 seconds under the conditions of a sealing bar area of 200 mm x 10 mm, 180°C, and 0.4 MPa to form a seal part. The sealed sample was then cut to a width of 15 mm. Finally, as shown in FIG. 5, one end of each laminate stacked above and below in the cut sample was fastened to the upper and lower jigs of a measuring device (UTM, Zwick), and then pulled in the vertical direction at a speed of 5 mm / min to measure the maximum tensile strength when the seal part was broken. The measurement results are shown in Table 2 below.
[0118] FIG. 5 shows how the breaking strength of a seal portion produced from a pouch film laminate according to the present invention is measured.
[0119] The measurement results of Experimental Examples 1 to 4 are shown in Table 2 below.
[0120] [Table 2]
[0121] According to Experimental Example 1, ΔY was measured to be 82.5% in Example 1, 108.3% in Example 2, 125% in Comparative Example 1, 150% in Comparative Example 2, and 65.1% in Comparative Example 3. That is, ΔY in Examples 1 and 2 was within the numerical range of 66% to 120% which is the reference value of the present invention, whereas ΔY in Comparative Examples 1 to 3 was measured to be outside the numerical range of 66% to 120% which is the reference value of the present invention.
[0122] On the other hand, the difference in yield strength between the first sealant layer and the second sealant layer was measured to be 6.6 N / 15 mm in Example 1, 7.8 N / 15 mm in Example 2, 8.5 N / 15 mm in Comparative Example 1, 9 N / 15 mm in Comparative Example 2, and 9.9 N / 15 mm in Comparative Example 3. That is, the difference in yield strength between the first sealant layer and the second sealant layer in Examples 1 and 2 was measured to be smaller than the reference value of 8 N / 15 mm in the present invention, whereas the difference in yield strength between the first sealant layer and the second sealant layer in Comparative Examples 1 to 3 was measured to be larger than the reference value of 8 N / 15 mm in the present invention.
[0123] According to Experimental Example 2, the peel strength between the gas barrier layer and the first sealant layer was measured to be 24 N / 15 mm in Example 1, 23.6 N / 15 mm in Example 2, 23 N / 15 mm in Comparative Example 1, 22 N / 15 mm in Comparative Example 2, and 20 N / 15 mm in Comparative Example 3. Therefore, the pouch-type battery cases manufactured by heat-sealing the pouch film laminates of Examples 1 and 2 have superior seal strength to the pouch-type battery cases manufactured by heat-sealing the pouch film laminates of Comparative Examples 1 to 3.
[0124] According to Experimental Example 3, no peeling was observed between the first sealant layer and the second sealant layer in the pouch film laminates produced in Examples 1 and 2, whereas peeling was observed between the first sealant layer and the second sealant layer in the pouch film laminates produced in Comparative Examples 1 to 3. Thus, the pouch-type battery cases produced by heat-sealing the pouch film laminates of Examples 1 and 2 have superior seal strength to the pouch-type battery cases produced by heat-sealing the pouch film laminates of Comparative Examples 1 to 3.
[0125] According to Experimental Example 4, the breaking strength of the seal portion manufactured using the pouch film laminates of Examples 1 and 2 was measured to be significantly higher at both 25° C. and 60° C. than the breaking strength of the seal portion manufactured using the pouch film laminates of Comparative Examples 1 to 3. Therefore, the pouch-type battery cases manufactured by heat-sealing the pouch film laminates of Examples 1 and 2 have superior seal strength to the pouch-type battery cases manufactured by heat-sealing the pouch film laminates of Comparative Examples 1 to 3. [Explanation of symbols]
[0126] 100 Pouch film laminate 110 Base material layer 120 Gas Barrier Layer 130 Sealant Layer 132 First sealant layer 134 Second sealant layer 210 Seal part 300 Secondary battery 310 Pouch-type battery case 320 Case 1 322 Cup section 324 Containment Space 330 Case 2 332 Cup section 340 Bridge section 350 Seal part 360 electrode assembly 370 Electrode tab 372 Positive tab 374 Negative electrode tab 380 Electrode Lead 382 Positive lead 384 Negative lead 390 Insulation
Claims
1. A pouch film laminate in which a base layer, a gas barrier layer, and a sealant layer are laminated in this order, The sealant layer comprises: a first sealant layer disposed adjacent to the gas barrier layer; and A second sealant layer is laminated on the first sealant layer. Including, A pouch film laminate, wherein ΔY according to the following formula 1 is 66% to 120%. [Equation 1] ΔY={(yield strength of second sealant layer−yield strength of first sealant layer) / yield strength of first sealant layer}×100
2. 2. The pouch film laminate according to claim 1, wherein the difference between the yield strength of the first sealant layer and the yield strength of the second sealant layer is 8 N / 15 mm or less.
3. 10. The pouch film laminate of claim 1, wherein the first sealant layer has a yield strength less than a yield strength of the second sealant layer.
4. The pouch film laminate of claim 1, wherein the first sealant layer has a yield strength of 7 N / 15 mm to 15 N / 15 mm.
5. The pouch film laminate according to claim 1, wherein the second sealant layer has a yield strength of 10 N / 15 mm to 30 N / 15 mm.
6. The pouch film laminate according to claim 1, wherein a thickness ratio of the first sealant layer to the second sealant layer is 1:0.3 to 1:
3.
7. The pouch film laminate according to claim 1 , wherein the first sealant layer has a thickness of 10 μm to 60 μm.
8. The pouch film laminate according to claim 1 , wherein the second sealant layer has a thickness of 20 μm to 70 μm.
9. 10. The pouch film laminate of claim 1, wherein the first sealant layer and the second sealant layer comprise polypropylene.
10. The pouch film laminate according to claim 9, wherein the first sealant layer and / or the second sealant layer further comprises at least one of a carbon fiber, a glass fiber, and an aramid fiber.
11. The pouch film laminate of claim 1 , wherein the gas barrier layer comprises aluminum.
12. 2. The pouch film laminate of claim 1, wherein the peel strength between the gas barrier layer and the first sealant layer is greater than 23 N / 15 mm.
13. A pouch-type battery case comprising the pouch film laminate according to any one of claims 1 to 12; and A secondary battery including an electrode assembly housed inside the pouch-type battery case.
14. the pouch-type battery case includes a seal portion, The secondary battery according to claim 13 , wherein the breaking strength of the seal portion measured at 25° C. is 100 N / 15 mm or more.
15. the pouch-type battery case includes a seal portion, The secondary battery according to claim 13 , wherein the breaking strength of the seal portion measured at 60° C. is 80 N / 15 mm or more.
16. A method for producing the secondary battery according to claim 14, comprising the steps of: The method comprises laminating two of the pouch film laminates so that the second sealant layers of each laminate are in contact with each other, and then sealing the laminate at 180°C and 0.4 MPa for two seconds to form the sealed portion.
17. A method for producing the secondary battery according to claim 15, comprising the steps of: The method comprises laminating two of the pouch film laminates so that the second sealant layers of each laminate are in contact with each other, and then sealing the laminate at 180°C and 0.4 MPa for two seconds to form the sealed portion.
Citation Information
Patent Citations
Aluminum-plastic film for flexible package of lithium battery and preparation method thereof
CN112793253A
Battery
JP1997120804A
Packaging material for battery
JP2014170720A
Packaging material for batteries
JP2015050075A
Outer package material for power storage device and power storage device
JP2016081869A